Respon Pertumbuhan dan Hasil Padi (Oryza sativa L.) Dengan Pengaturan Jarak Tanam dan Jumlah Bibit yang Berbeda - Bawani, Sokib; Hera, Novita; Rosmaina, Rosmaina (Agropross : National Conference Proceedings of Agriculture, 2023)
The rice plant (Oryza sativa L.) is the main food crop for most of the Indonesian population, with the increasing population of Indonesia, the need for rice is increasing. One way to increase the growth of rice plants is by adjusting the spacing and number of perforated seeds. This study aims to determine the spacing and the number of seeds that are suitable for planting rice. This research has been carried out in the village of Kota Baru Reteh, Keritang District, Inhil. This research is a factorial randomized block design (RBD) with two factors, the first is the spacing of A1: 20 cm x 20 cm, A2: 25 cm x 25 cm, A3: 30 cm x 30 cm, A4: 35 cm x 35 cm and the second: second number of perforated seeds B1: 1 perforated seed B2: 2 perforated seeds B3: 3 perforated seeds A4: 4 perforated seeds. The results showed that there was an interaction between planting distance and the number of perforeted seeds on the number of productive tillers per clump, wet grain weight, dry defecationand 1000 grain weight but there was no interaction with plant height. Based on the research that has been carried out, it can be concluded that the spacing of 30 cm x 30 cm and the number of seeds of 1 perforated seed showed the best results